Equity valuation : Ferro Corporation - Ascensão, António Brás Monteiro (2019)
This dissertation’s objective is to present a practical implementation of the state-of-the-art equity investment methods analysed throughout the literature review. The investment analysis was set upon Ferro Corporation, a specialty chemicals USA-based global company. After carefully analysing the firm’s business operation alongside with industry and macroeconomic trends, it was possible to reach to the company’s fair value through the DCF and relative valuation methods. The final value estimation was set by only taking into consideration the DCF method, reaching a valuation of $22.43, representing a 2.19% premium over the company’s market price as of 31 August 2018, leading to a hold recommendation which is complemented by the relative valuation model. Finally, the present dissertation is compared with an equity research report produced by Deutsche Bank, following an examination between the differences on the used assumptions and methodologies.